2014
DOI: 10.1016/j.ijsu.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient management of biliary colic: A prospective observational study of prescribing habits and analgesia effectiveness

Abstract: The range of drugs prescribed for biliary colic is extensive with little evidence base. In this study NSAIDs were the most effective analgesia for patients with severe pain. In the absence of contraindications to their use, physician education or guidance emphasizing the benefits of NSAIDs may potentially reduce symptomatic hospital presentation and admissions for biliary colic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In this trial, the following measures will be taken to strengthen quality control: (1) this study restricts participants to ages between 18 and 60 years and to being right handed, avoiding the impact of age and handedness on brain function and structure; (2) to get stable statistic power, 36 patients will be included in each group for clinical evaluation and 25 patients in each group for the central mechanism study; (3) all researchers will be uniformly trained to understand the design and process of the trial, and the acupuncture treatment will be performed by two licensed acupuncturists, who have received special and standardised training before the trial; (4) one technician will perform all scans in the same fNIRS machine according to the operation standard and the design of the study in the fixed condition, and, before being scanned, the mental state of each participant will be evaluated using the Zung Self-rating Anxiety Scale and Zung Self-rating Depression Scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this trial, the following measures will be taken to strengthen quality control: (1) this study restricts participants to ages between 18 and 60 years and to being right handed, avoiding the impact of age and handedness on brain function and structure; (2) to get stable statistic power, 36 patients will be included in each group for clinical evaluation and 25 patients in each group for the central mechanism study; (3) all researchers will be uniformly trained to understand the design and process of the trial, and the acupuncture treatment will be performed by two licensed acupuncturists, who have received special and standardised training before the trial; (4) one technician will perform all scans in the same fNIRS machine according to the operation standard and the design of the study in the fixed condition, and, before being scanned, the mental state of each participant will be evaluated using the Zung Self-rating Anxiety Scale and Zung Self-rating Depression Scale.…”
Section: Discussionmentioning
confidence: 99%
“…Gallstone disease is one of the most common gastrointestinal and biliary system disorders. 1 As the main manifestation of gallstone disease, biliary colic (BC) is severe pain in the right upper abdominal quadrant that attacks patients for at least 20-30 min. [2][3][4] In the developed world, 10%-15% of adults have gallstones, and BC occurs in 1%-4% of those with gallstones each year.…”
Section: Introductionmentioning
confidence: 99%
“…Gallstones are among the most common disorders of the digestive system that affect 10% of individuals [6,7]. More than 80% of the patients with gallstones have no sign and symptom, and 1-3% have symptomatic manifestations such as acute cholecystitis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics are used in cases of sepsis associated with gallstone disease (Royal College of Surgeons, 2016). Nonsteroidal anti-inflammatory drugs have been shown to be the most effective form of pain relief for patients who are being managed in the community or are waiting for surgical treatment (Johnston et al., 2014). In biliary colic, one study showed that diclofenac had the greatest effect on pain, and some patients showed a reduction in the development of acute cholecystitis following biliary colic (Kumar, Deed, Bhasin, Kumar, & Thomas, 2004; Masudi, Capitelli-McMahon, & Anwar, 2016).…”
Section: Managementmentioning
confidence: 99%